Modyfikacja metody klasyfikacji podziałowej opartej na kryteriach - Pełka, Marcin (Modification of criterion-B=based divisive clustering method, 2006)
The aim of this article is to present one of symbolic clustering methods, the criterion-based divisive clustering method, besides that article presents a modification of this method that will allow to clustering symbolic objects with different variable types. The article will compare in the empirical part the clustering of a car market with modified and unmodified method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 246-255